2009
DOI: 10.1007/s11160-009-9146-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary fatty acids profiles on the growth performance and body composition of juvenile tench (Tinca tinca (L.))

Abstract: Juvenile tench (initial weight of about 57 g) were fed feed supplemented with fish oil (group FO), linseed oil (group LO), peanut oil (group PO), or rapeseed oil (group RO) containing 47% protein and 12% fat for 55 days. The inclusion of the tested oils was 50 g kg -1 (42% total crude lipids in diets). No significant differences were noted in the fish growth performance. The proximate composition of the whole fish bodies and the viscera (water, protein, fat, ash) was similar in all the dietary treatments (P [ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
(25 reference statements)
3
8
0
Order By: Relevance
“…Our findings are in agreement with previous studies in cyprinid species (goldfish, Carassius auratus; common carp, C. carpio; grass carp, Ctenopharyngodon idella; tench, Tinca tinca) in which vegetable oils did not affect the chemical composition of these fish over either short or long-term periods (Steffens et al, 1995;Pozernick and Wiegand, 1997;Du et al, 2008;Zakęś et al, 2010). In this study, the changes of protein level in feed showed significant influence on the chemical composition of carp fillets.…”
Section: Proximate Composition Of Common Carp Filletssupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are in agreement with previous studies in cyprinid species (goldfish, Carassius auratus; common carp, C. carpio; grass carp, Ctenopharyngodon idella; tench, Tinca tinca) in which vegetable oils did not affect the chemical composition of these fish over either short or long-term periods (Steffens et al, 1995;Pozernick and Wiegand, 1997;Du et al, 2008;Zakęś et al, 2010). In this study, the changes of protein level in feed showed significant influence on the chemical composition of carp fillets.…”
Section: Proximate Composition Of Common Carp Filletssupporting
confidence: 93%
“…Several studies have shown that total replacement of FO with vegetable oils, including RO in diets of cyprinid fish species, has no negative effects on fish growth and growth parameters (Turchini et al, 2007;Kukačka et al, 2009;Zakęś et al, 2010). In agreement with the previous studies, the present experiment showed no negative effect of total inclusion of RO instead of FO on production parameters and growth of common carp reared in cages under natural atmospheric conditions.…”
Section: Production Performancesupporting
confidence: 91%
See 2 more Smart Citations
“…Emphasis is being given on the strategies for lowering the production cost from aquaculture through better utilization of feeds by fish. Similarly, replacement of FO by vegetable oils also did not reduce the performance of some fish species (Zak ȩś et al 2010;Ljubojević et al 2015). Blends of plant protein sources as the FM replacement in fish feeds have been successful to a large extent in several aquaculture species (Gatlin et al 2007;Tacon and Metian 2008;Hardy 2010).…”
mentioning
confidence: 99%